Dampak Spasial Berdirinya Kawasan Industri Candi Terhadap Penggunaan Lahan di Wilayah Kecamatan Ngaliyan Kota Semarang - Muntaman, Putra; Juhadi, Juhadi; Heri, Tjahjono (Geo-Image, 2019)
This study aimed to find out the spatial impact of the establishment of temple industrial area on the land use in Ngaliyan. Quantitative approach with spatial data processing, weighting and descriptive methods was used in this research. The establishment of industrial areas would make either positive impacts or negativer ones; it would require certain amountof land, so that land – use changes occurred, guava orchards transformed into industrial area. By knowing this industrial area development, some impacts could be decreased and its RTRW system(  administrative division) could be obeyed. The research results showed that the most significant land use in 2005 until 2015 was for industrial arears of 5.59 ha, and for the residential areas increased to 2.75 ha. As for the carrying capasity in Ngaliyan, it had a medium one so that it had a moderate interpretation as well; and the impacts of the land – use changes underwent some condition changes due to the development of industrial areas around the templen in the amount of -1,33 %.